Policies on prevention and eradication of land mafia: Agrarian reform in Indonesia - GINTING, D (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT One of the main causes of land disputes is due to the actions of the land mafia. The purpose of this research is to analyze and formulate policies on the prevention and eradication of the land mafia in Indonesia. The method used is qualitative research, and this type of research is included in the category of library research, and the research approach is descriptive-analytic. While the data analysis technique in this study uses the Miles and Huberman models, the conclusion from this study is that land dispute resolution cannot be made legally in Anich.